Does Working-Memory Training Given to Reception-Class Children Improve the Speech of Children at Risk of Fluency Difficulty? - Howell, Peter; Chua, Li Ying; Yoshikawa, Kaho; Tang, Hannah Hau Shuen; Welmillage, Taniya; Harris, John; Tang, Kevin (Frontiers in Psychology, 2020)
Procedures were designed to test for the effects of working-memory training on children at risk of fluency difficulty that apply to English and to many of the languages spoken by children with English as an Additional Language in UK schools. Working-memory training should: (1) improve speech fluency in high-risk children; (2) enhance non-word repetition (phonological) skills for all children; (3) not affect word-finding abilities. Children starting general education (N=232) were screened to identify those at risk of fluency difficulty. Children were selected who were at high-risk (12), or low-risk (27) of fluency difficulty. For the low-risk children 10 received, and 17 did not receive, the working-memory training. All children in the treatment groups received working-memory training over a two-week period. For the high-risk group, fluency improved and lasted for at least a week after the end of the study. Phonological skills improved in this group and in the low-risk group who received the training and the improvements continued for at least a week. The low-risk group who did not receive working-memory training showed no improvements, and no group improved word-finding ability.